Growth Hormone Treatment in Children With Prader-Willi Syndrome: Three Years of Longitudinal Data in Prepubertal Children and Adult Height Data From the KIGS Database - Bakker, Nienke E.; Lindberg, Anders; Heissler, Joseph; Wollmann, Hartmut A.; Camacho-Hübner, Cecilia; Hokken-Koelega, Anita C. (The journal of clinical endocrinology and metabolism, 2017)
Longitudinal data of children with Prader-Willi syndrome (PWS) treated with genotropin were registered in the Pfizer International Growth Database (KIGS). To evaluate efficacy and safety of growth hormone (GH) treatment in a large group of children with PWS. Data registered in KIGS from 1987 to 2012. Worldwide retrospective cohort study. Patients included 522 prepubertal children treated with GH for three years and 173 children who had reached adult height. Safety analysis included 2332 children. Intervention involved GH treatment. Height standard deviation score (SDS), body mass index (BMI) SDS, occurrence of serious adverse events, and deaths reported in KIGS. In prepubertal children, mean (standard deviation) height SDS improved to -0.31 (1.34) (P < 0.05) during three years of GH treatment. In the adolescent group, height SDS improved until the start of puberty to -0.22 (1.31) (P < 0.05) but had a loss of -0.77 (0.81) during puberty, resulting in a mean adult height SDS of -1.19 (1.37). Total height gain was 0.95 (1.32) SDS. BMI SDS increased in the prepubertal group from 1.11 (2.09) to 1.53 (1.43) (P < 0.05) and did not significantly change in the adolescent group, who had a BMI SDS at an adult height of 1.78 (1.26). KIGS contained 12 death reports. GH treatment in children with PWS significantly improves linear growth. BMI remains on average below +2 SDS, in contrast to the natural course of increasing obesity in PWS. Safety should be closely monitored in children with PWS, with and without GH treatment.